Handbook of reflector antennas and feed systems. Volume 1 : Theory and design of reflectors - Sudhakar Rao, B.; Shafai, Lotfollah; Sharma, Satish; Kane, Vicki; Aliamus, Michael (Artech House, 2013)
This is the first truly comprehensive and most up-to-date handbook available on modern reflector antennas and feed sources for diversified space and ground applications. There has never been such an all-encompassing reflector handbook in print, and no currently available title offers coverage of such recent research developments. The Handbook consists of three volumes. Volume I provides a unique combination of theoretical underpinnings with design considerations and techniques. The need for knowledge in reflector antennas has grown steadily over the last two decades due to increased use in spa.